2016
DOI: 10.3171/2015.7.jns142666
|View full text |Cite
|
Sign up to set email alerts
|

Different aspects of dysexecutive syndrome in patients with moyamoya disease and its clinical subtypes

Abstract: obJective Dysexecutive syndrome is common in patients with moyamoya disease (MMD), a chronic cerebrovascular disease that is characterized by stenosis of the bilateral internal carotid arteries and progressive collateral revascularization, and MMD can be classified as ischemic or hemorrhagic according to the disease presentation and history. In this study, the authors aimed to determine which aspects of executive function are impaired in patients with MMD, in addition to the specific dysexecutive functions pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 34 publications
3
14
0
Order By: Relevance
“…Anatomical location of advanced cognitive function has undergone intensive investigation. Despite a few studies reporting a correlation between hemodynamic compromise in temporal lobe and cognitive impairment (26,30), more researchers found that regions in the frontal lobe are linked to executive function, both from aspects of hemodynamics and metabolism (4,15,31,32). Using multivariate linear regression to adjust for confounders, we found that the average CBF of the left temporal lobe independently associated with processing speed.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Anatomical location of advanced cognitive function has undergone intensive investigation. Despite a few studies reporting a correlation between hemodynamic compromise in temporal lobe and cognitive impairment (26,30), more researchers found that regions in the frontal lobe are linked to executive function, both from aspects of hemodynamics and metabolism (4,15,31,32). Using multivariate linear regression to adjust for confounders, we found that the average CBF of the left temporal lobe independently associated with processing speed.…”
Section: Discussionmentioning
confidence: 65%
“…Correlation between cerebral blood perfusion and cognitive function in adult MMD patients has been investigated, and hypoperfusion in several specific brain regions had been identified as responsible for corresponding cognitive deficits. Both cerebral vascular reserve and CBF in the frontal lobe were proved to correlate to executive functioning in adult MMD patients (4,15). Moreover, the associations between CBF in several brain areas, including left ventral middle cerebral artery territory and bilateral dorsal anterior cerebral artery territory, and multiple aspects of cognitive function had also been reported (27).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Cognitive dysfunction resulting from MMD has begun to garner the attention of researchers studying the disorder [ 14 , 15 , 18 ]. However, despite the increasing use of rs-fMRI to investigate brain function in other cognitive disorders, few published studies have used rs-fMRI to investigate cognitive dysfunction in MMD, [ 17 , 20 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moyamoya disease (MMD) is a rare cerebrovascular disease characterized by a fine vascular network (“moyamoya vessels”) at the base of the brain, which results from stenosis or occlusion of the terminal branches of the internal carotid arteries [ 13 ]. In addition to cerebral stroke, patients with this condition may present with cognitive impairments, such as executive dysfunction, impaired working memory, and attention deficit, likely as a result of chronic ischemic injury [ 14 16 ]. Early detection of altered brain function due to ischemia could potentially improve the quality of life of such patients, in whom chronic ischemia can lead to suboptimal brain development in children and adolescents, and/or the early onset of cognitive decline in adults [ 14 18 ].…”
Section: Introductionmentioning
confidence: 99%